(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Project management knowledge contains a wide range of information that can be accumulated from theory and practice. This knowledge is not always readily available to project manager and that can leave a significant impact on project management efficiency and success. Therefore, this knowledge is necessary to store in the project management knowledge repository and then to retrieve it when necessary. To find this knowledge it is necessary to define attributes for searching relevant projects and knowledge associated with these projects. The objective of this paper is to develop a set of project classification attributes that can be used to describe project characteristics and use them in similarity definition. The project classification attributes are defined as a part of the architecture of project management knowledge retrieval. They are identified by analyzing several project management methodologies and are validated by classifying twenty two empirical information technology projects.